The MARES Platform: Support for Transactional and Fault-tolerant Execution of Mobile Agent-based Applications - Silva, Flávio M. Assis; Macêdo, Raimundo J. A.; Freitas, Ana Vitoria Piaggio (Anais do Workshop de Testes e Tolerância a Falhas (WTF), 2003)
Support for transactional behaviour and fault tolerant executions of mobile agent-based applications is a fundamental issue in the development of mobile agent systems. We are developing the MARES platform, which supports the modelling of mobile agent-based applications as distributed transactions. The executions of mobile agent-based transactions on top of the MARES platform are fault-tolerant, in the sense that if the location in the distributed environment where a part of a global transaction is being executed becomes faulty for a long time, the system performs a recovery procedure to resume the execution of that part of the transaction at another location. In this paper we present the transaction model used in the MARES platform, we outline the interface for modelling mobile agent-based transactions, and we discuss alternatives for implementing mobile agent fault tolerance that increase the level of flexibility for modelling reliable mobile agent-based applications when compared with previously proposed approaches.